Intrasplenic Transplantation of Bioencapsulated Mesenchymal Stem Cells Improves the Recovery Rates of 90% Partial Hepatectomized Rats - Zun Chang Liu; Thomas Ming Swi Chang (Stem Cells International)
Mesenchymal stem cells (MSCs) derived from bone marrow can secrete cytokines and growth factors and can transdifferentiate into liver cells. We transplanted polymeric membrane bioencapsulated MSCs into the spleens of 90% partial hepatectomized rats. This resulted in 91.6% recovery rates. This is compared to a recovery rate of 21.4% in the 90% hepatectomized rats and 25% in the 90% hepatectomized rats receiving intrasplenic transplantation of free MSCs. After 14 days, the remnant livers in the bioencapsulated MSCs group are not significantly different in weight when compared to the sham control group. From day 1 to day 3 after surgery, in the bioencapsulated MSCs group, the plasma HGF and IL-6 were significantly higher than those in the free MSCs group and control group (P<0.01); plasma TNF-α was significantly lower (P<0.001). We concluded that the intrasplenic transplantation of bioencapsulated MSCs significantly increases the recovery rates of 90% hepatectomized rats. It is likely that the initial effect is from proliver regeneration factors followed later by the transdifferentiated hepatocyte-like cells. However, histopathological analysis and hepatocyte proliferation study will be needed to better understand the regenerative mechanisms of this result. This study has implications in improving the survival and recovery of patients with very severe liver failure due to hepatitis, trauma, or extensive surgical resection.